SANKSI UNI EROPA TERHADAP RUSIA ATAS PELANGGARAN TERITORIAL UKRAINA: PENDEKATAN MULTI-TUJUAN - Faisal Nurdin Idris; Muhammad Rafif Mu’tashim (Universitas Jenderal Ahmad Yani, 2023)
Sanctions or restrictive measures have become a useful tool of the European Union's Foreign and Security Policy (CFSP) in responding to Russia’s violation of Ukraine’s territorial integrity. While there are shortcomings in existing literature on how the EU as a supranational organization imposes sanctions, this article provides accounts of going beyond the rigid behavioral change approach. Drawing from the multi-purpose approach, highlighting three functions of sanctions, namely coercing, constraining, and signaling/stigmatizing, we argue that these three functions of sanctions can better explain the imposition and extension of EU sanctions on Russia during the period from 2014-2016. If coercive sanctions seem to be less likely to work in changing Russia’s behavior in a given context, constraining sanctions and signaling/stigmatizing sanctions can take a greater role in suppressing Russia both to a domestic audience and the international community, stigmatizing or isolating Russia for violating international norms and law.